Implementation of Positive Affirmations Using Gratitude Journal to Reduce Suicide Risk in Adolescent Schizoaffective Patient: A Case Report - Elfani, Karisha Citra; Widianti, Efri; Sriati, Aat (Universitas Padjadjaran, 2024)
Suicide risk is one of the impacts as well as the final diagnosis of schizoaffective disorder. Schizoaffective disorder is associated with an increased risk of death that is 2 to 2.5 times higher than the general population. Suicide prevalence tends to be more prominent among individuals in younger age groups. This study was conducted with the aim of identifying the application of gratitude journaling as a positive affirmation exercise in patients with suicide risk. This study uses a case report design presented in the form of implementing an intervention, namely gratitude journal as a modification of positive affirmations with the subject of one patient with depressive type schizoaffective disorder with suicide risk. The data collection techniques used were observation, interviews, and filling out questionnaires using the Indonesian version of the Revised-Suicide Ideation Scale (R-SIS) instrument to measure suicidal ideation scores. The results of the study showed a decrease in suicidal ideation score from 41 to 11. The application of gratitude journal showed a decrease in suicidal ideation observed from the decrease in score. It is hoped that further research can be carried out with better or higher research methods to identify the efficacy of this intervention in reducing the risk of suicide.Keywords: Adolescent, gratitude journal, schizoaffective, suicide risk